Educational Cognitive Technologies as Human Adaptation Strategies - Marja Nesterova (International Society of Philosophy and Cosmology, 2017)
Modernity is characterized by profound changes in all spheres of human life caused by the global transformations on macro and micro levels of social reality. These changes allow us to speak about the present as the era of civilizational transition in the mode of uncertainty. Therefore, this situation demands qualitative transformations of human adaptive strategies and educational technologies accordingly. The dominant role in the dynamics of pedagogics and andragogy's landscape belongs to transformative learning. The transformative learning theory is considered as the relevant approach to education of the individual, which is able to become an autonomous communicative actor of the social complexity. The article considers the cognitive technologies of social cohesion development and perspectives of their implementation in the educational dimension. In addition to implementing the principles of inclusion, equity in education, an important factor for improving social cohesion, stability and unity of society is the development of cognitive educational technologies. The key factors and foundations for the cognitive educational technologies are transversal competencies. They create the conditions for civil, public dialogue, non-violent type of communication. These "21st century skills" are extremely important for better human adaptation. One of the aspects and roots of social adaptation is social cohesion. Mutual determinations and connections between social cohesion development and transversal competences have been shown. The perspective direction of further researches is to find a methodological base for the further development of cognitive education technologies and platform for realization of innovative services for educational programs. New educational paradigm offers the concept of human adaptation as cognitive effectiveness and how to reach it through educational technologies. The article includes topics of creative thinking, teambuilding abilities, effective decision-making, engagement in the learning and teaching processes, cognitive skills improvement, social cohesion abilities, etc